Analysis of Airspace Sectorization Effectiveness in the East Sector of Jakarta FIR Area Control Centre - Rizky Dwi Utami; Rahmawati Sukra; Martha Saulina (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study analyzes the effectiveness of airspace sector division at the Area Control Centre (ACC) Sector East, Jakarta Flight Information Region (FIR), in supporting the operational efficiency of Air Traffic Controllers (ATCs). The research aims to evaluate the current airspace sectorization in terms of operational, technical, and human resource aspects to determine whether the existing configuration meets the growing traffic demand. Using a quantitative descriptive and evaluative approach, the study focuses on two main variables: ATC workload and inter-sector coordination. Data were collected from 58 ATC personnel at the Jakarta Air Traffic Service Centre (JATSC) through a Likert-scale questionnaire. The data were analyzed using statistical methods including Pearson correlation and multiple linear regression. The results reveal that both workload and inter-sector coordination significantly affect the effectiveness of sector division, with workload having a stronger influence. The findings indicate that unbalanced workload distribution and limited coordination efficiency reduce overall sector performance. The study concludes that an adaptive and dynamic sectorization model is needed to ensure balanced workload, enhanced communication, and improved operational safety at ACC-East Jakarta